Dietary carbohydrate and food processing affect the digestive physiology of Piaractus mesopotamicus - Honorato, C. A.; de Almeida, L. C.; Camilo, R. Y.; Moraes, G.; Nunes, C. D.S.; Carneiro, D. J. [UNESP] (Hindawi, 2016)
The responses of the digestive physiology of juvenile pacu to different diet processing were studied. Fish were fed with isoproteic diets with 260 g kg−1 of crude protein (CP) containing different levels of carbohydrate (DCh) (400 or 500 g kg−1), and two diet processing (pelletization or extrusion) for 90 days. Fish fed with extruded diets showed decrease of the gastrointestinal transit time (GI transfer) and of the amylase activity, but maltase activity did not alter. Protease activity of intestine depicted increase when the DCh was raised. The increase of DCh also caused enhancement of the apparent digestibility coefficient of CP (ADCCP) in fish fed with extruded diets. Fish fed with pelletized diets showed increase of the amylase activity in pyloric caecum independently of the dietary carbohydrate level. No interaction was observed between dietary carbohydrate level and diet processing. Maltase activities from the stomach and intestine of pacu were not responsive to the carbohydrate level. The extrusion process improved the carbohydrate availability and the digestion efficiency of protein in pacu. Digestive enzymes of pacu were modulated either by nutrients or diet processing.
Keywords: digestibility; digestive enzymes; extrusion; pacu; pelletization; starch gelatinization